2020
DOI: 10.1002/aoc.5858
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of ZnO nanoparticles from a Zn(II) coordination polymer: Structural characterization, optical properties and photocatalytic activity

Abstract: A zinc coordination polymer derived from pyridine‐2,6‐dicarboxylate (PDC), {[Zn2(PDC)2]}n, was successfully prepared via conventional, sonication and microwave‐irradiation methods. The composition and characteristics of the obtained coordination polymers (CPs) were investigated by elemental analysis, TGA/DTA, X‐ray diffraction and spectroscopic techniques. The so obtained CPs were heat‐treated in the air at 600 °C for 2 h to produce ZnO of nanosized particles (NPs). It is of interest to note that the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Indeed, sonolysis is known of its ability for introducing disaggregation and reducing the size of the synthesized materials via introducing high pressure and temperature spots during synthesis in the reaction medium. [ 30–34,54–57 ] Additionally, it was confirmed that chemical and sonochemical synthetic routes for the complex formation resulted not only in coordination compounds of different sizes but also in obtaining derived NPs of different sizes. [ 30,58 ] The tetra‐coordinate zinc complexes especially those with salicylaldimine ligands are usually tetrahedral (SP 3 hybridization), and the involvement of salicylaldimine ligands in coordination was reported to be via the imine nitrogen and the hydroxyl oxygen atoms in a monobasic manner.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, sonolysis is known of its ability for introducing disaggregation and reducing the size of the synthesized materials via introducing high pressure and temperature spots during synthesis in the reaction medium. [ 30–34,54–57 ] Additionally, it was confirmed that chemical and sonochemical synthetic routes for the complex formation resulted not only in coordination compounds of different sizes but also in obtaining derived NPs of different sizes. [ 30,58 ] The tetra‐coordinate zinc complexes especially those with salicylaldimine ligands are usually tetrahedral (SP 3 hybridization), and the involvement of salicylaldimine ligands in coordination was reported to be via the imine nitrogen and the hydroxyl oxygen atoms in a monobasic manner.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30–34,54–57 ] Additionally, it was confirmed that chemical and sonochemical synthetic routes for the complex formation resulted not only in coordination compounds of different sizes but also in obtaining derived NPs of different sizes. [ 30,58 ] The tetra‐coordinate zinc complexes especially those with salicylaldimine ligands are usually tetrahedral (SP 3 hybridization), and the involvement of salicylaldimine ligands in coordination was reported to be via the imine nitrogen and the hydroxyl oxygen atoms in a monobasic manner. [ 59–61 ] The analytics only showed negligible differences between the nonsonicated and sonicated complex regarding the CHN composition, FT‐IR data and DMF solution electrical conductivity clearing the same formula of [ZnL 2 ] for the complex in both cases (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The negatively charged WGE ZnO NPs enable them to efficiently adsorb the cationic stains and facilitate electrochemical interactions between the reactive radicals and stain molecules. On irradiation with visible light, photons bearing energy greater than or equal to 2.72 eV will excite the electrons from the valence band to the conduction band generating electron‐hole pairs [64] . Holes produced in the valence band react with H 2 O or OH − to form hydroxyl radicals (OH⋅).…”
Section: Resultsmentioning
confidence: 99%